Evaluasi Pembelajaran Membaca Bahasa Arab Siswa Kelas Viii Mts Miftahul Khair Hartaco - Mujahidah Rasuna Said, Uswah; Rizqi Ramadhan, Aji; Syihabuddin, Syihabuddin; Haidar, Alfan (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2025)
This study examines the Arabic reading ability of eighth-grade students at MTs Miftahul Khair Hartaco. This research employs a mixed-methods approach, combining quantitative and qualitative descriptive analysis. The instruments used include observation, questionnaires, and interviews. The evaluation was carried out through pronunciation and sentence tests, and factors that cause problems in learning Arabic were identified.  The results indicate that students’ hijaiyyah letter pronunciation in the vocabulary test was at a moderate level (61.90%), whereas their pronunciation in conversational sentences was significantly weaker (42.25%). Overall, their Arabic pronunciation ability was categorized as deficient, with an average score of 53.56%. The study identifies internal factors such as low student interest and motivation, while external challenges include limited learning resources and a lack of varied teaching methods.  This study concludes that improving Arabic reading skills requires a holistic approach that addresses both internal and external factors. Recommendations include developing innovative teaching strategies, integrating technology in learning, and enhancing instructional materials to foster better engagement and reading proficiency.